A case study for industrial centrifugal pump as a vibration source for macro-scale electromagnetic energy harvesting - Ul Haq Gilani, S.F. (Institute of Electrical and Electronics Engineers Inc., 2017)
This research proposes the industrial centrifugal pump as a potential application for vibration energy harvesting. The energy harvested from the centrifugal pump will be utilized in the condition monitoring system of the pump itself. The complete test setup along with the vibration results from an industrial centrifugal pump are presented. The most optimum position on the pump is proposed based on the highest vibration level achieved among all six tested positions. Furthermore, a study is performed on the power requirement of currently available wireless vibration sensors in the market. Based on the study, an estimate of expected power requirement from the energy harvester is presented. Various electromagnetic type energy harvesters are reviewed and compared in terms of FoMv (volume figure of merit) in order to find out the most optimum design and techniques. Lastly, based on all the test results and studies performed, an electromagnetic energy harvester design is proposed for the application of the centrifugal pump keeping the physical dynamics in scope. © 2016 IEEE.